Instrumentation and Aerothermal Post-Flight Analysis of the Rocket Technology Flight Experiment ROTEX-T - Thiele, Thomas; Gülhan, Ali; Olivier, Herbert (Journal of Spacecraft and Rockets, 2018)
Based on experience gathered during the hypersonic flight experiments SHEFEX-I and SHEFEX-II the German Aerospace Center (DLR) performed the flight experiment ROTEX-T (ROcket Technology EXperiment-Transition). ROTEX-T was successfully launched on 19th July 2016 at 06:05 am CEST from the Esrange Space Center near Kiruna in northern Sweden. ROTEX-T was a low cost flight experiment mission without inertial measurement unit, reaction control system or parachute. The payload reached an altitude of 183 kilometers, performed a ballistic re-entry with a total flight time of approximately 446 seconds and was afterwards recovered by helicopter. A unique and modular data acquisition system with sampling rates of 20 Hz, 1 kHz, 10 kHz and 2000 kHz was developed for ROTEX-T to study also instationary aerothermal phenomena.